Workshop on TikTok Utilization as Digital Marketing Media for the Nasyiatul Aisyiyah Entrepreneur Association (APUNA) Klaten - Winny Perwithosuci; Didit Purnomo; Sitti Retno Faridatussalam; Nur Hidayah; Inda Fresti Puspitasari; Mochamad Hasan Makmur Farid (PT FORMOSA CENDEKIA GLOBAL, 2023)
Digital marketing is marketing activity using the internet, either utilizing the website or social media. In 2023, TikTok users are 1.7 billion in the world. This community service activity aims to provide knowledge to members of the Klaten Regency Nasyiatul Aisyiyah Entrepreneurs Association (APUNA) regarding the use of TikTok as a digital marketing tool by using a new feature called TikTok Shop. The community service activities employed training method and were followed by discussion and practice sessions. This activity ran smoothly, and the participants who attended understood and practiced the function of TikTok as social media for conducting digital marketing.